1991
DOI: 10.1177/000456329102800209
|View full text |Cite
|
Sign up to set email alerts
|

Transferrinuria in Type 2 Diabetes: The Effect of Glycaemic Control

Abstract: SUMMARY. Urinary excretion rates of transferrin, albumin. N-acetyl-8-Dglucosaminidase (NAG) and a-I-microglobulin (A1 M) were measured in type 2 (non-insulin-dependent) diabetic patients at diagnosis and after 6 and 12 weeks treatment. Initially 21 (53%) patients had elevated transferrin excretion rates. The proportion of patients with raised transferrin excrction rates fcll to 30% at 6 wccks and 20% at 12 wecks with treatment of diabetcs. At diagnosis I 1 (28%) paticnts had elevated albumin excretion rates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Urinary ␣ 1 -microglobulin was also directly related to poorer control of diabetes, as measured by HbA 1c , fasting plasma glucose, and 2-h postprandial glucose, which is similar to findings in Caucasian populations (17,18). A study in Japan found that the development or progression of early diabetic nephropathy was inhibited by good glucose control (28).…”
Section: Descriptive Profilesupporting
confidence: 78%
See 1 more Smart Citation
“…Urinary ␣ 1 -microglobulin was also directly related to poorer control of diabetes, as measured by HbA 1c , fasting plasma glucose, and 2-h postprandial glucose, which is similar to findings in Caucasian populations (17,18). A study in Japan found that the development or progression of early diabetic nephropathy was inhibited by good glucose control (28).…”
Section: Descriptive Profilesupporting
confidence: 78%
“…Urinary ␣ 1 -microglobulin has been found to be higher, when compared with normal control subjects, in both type 1 (12) and type 2 diabetic subjects (13) and present even without clinical nephropathy (14,15). In type 2 diabetic subjects, ␣ 1 -microglobulin excretion was directly correlated with albuminuria (16) and HbA 1c levels (17) and decreased with improved glycemic control (17,18). These studies, however, were conducted on Caucasian populations, and the number of subjects was small (Ͻ100).…”
mentioning
confidence: 99%
“…Similarly to our results, O'Donnell et al 23 found no correlation between urinary transferrin levels and glycemic control in the group of 40 DM2 patients at first day of the disease diagnosis and after 6 and 12 weeks of treatment. Urinary excretion rates of transferrin were measured, and they showed that urinary transferrin was not correlated with glycemic control.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, glycemic control in newly diagnosed type 2 diabetic patients can effectively decrease transferrinuria [59]. Further evidence of transferrinuria as a marker of diabetic microvascular complications is the fact that urinary transferrin excretion is higher in type 2 diabetic patients with retinopathy [42, 44].…”
Section: Transferrinmentioning
confidence: 99%
“…It is known that reabsorption of transferrin results in release of reactive iron [57], which can produce oxidative stress on the tubular epithelium. Several studies have shown that markers of proximal tubule damage (i.e., alpha-1-microglobulin and N-acetyl-beta-D-glucosaminidase (NAG)) and urinary transferrin excretion are associated in diabetic patients [40, 43, 44, 53, 59]. It is not clear if transferrinuria is secondary to decreased tubular reabsorption, or transferrin is the cause of tubular damage.…”
Section: Transferrinmentioning
confidence: 99%